KINERJA KEPALA DESA DALAM MENJALANKAN TUGAS DAN FUNGSI PELAYANAN PUBLIK DI DESA KORI KECAMATAN KODI UTARA KABUPATEN SUMBA BARAT DAYA - Yohanis Ndoda (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2021)
The duties and functions of the village head are intended to support the implementation of village development, namely carrying out the formulation and determination of policies, fostering initiatives, supervising the implementation of decisions and being responsible for the course of village development. But in reality, in the observations of researchers, the implementation of the duties, functions and obligations of the village head is still not running optimally. This is presumably due to several problems, especially the lack of facilities and infrastructure, the knowledge and skills of village heads, village officials and apparatus are still low, the affordability of public facilities and the level of public awareness is still very low. This study uses a qualitative research method with a descriptive approach. To obtain valid data and information, the researchers used interview, observation and documentation techniques. Research conducted by researchers shows that village officials and the community in general in Kori Village still have very little understanding of the concept of Regional and Village Autonomy. They have only just learned and become familiar with the term regional and village autonomy through radio broadcasts, television, newspapers and political speeches by officials and politicians, so that a detailed understanding of the intricacies of regional/village autonomy and its implementation seems to be lacking. In conclusion, the duties and functions of the Village Head in public services in Kori Village have been very good according to other village officials, but according to the community's assessment of how the Village Head works in the implementation of development, it is still not satisfactory because the Village Head is unable to establish good cooperation to encourage and mobilize the community and village officials to work together for good development goals